Bipolar Reduction and Behavioral Variability During the Mid-Late Holocene at Eagle's Nest, Mount Sinai Harbor, New York. (3rd April 2019) - Pargeter, Justin; Tweedie, Mark S.
ABSTRACT: Recent syntheses for the Long Island Sound region argue for long-term cultural continuity amongst Holocene coastal hunter-gatherers. These notions derive primarily from studies of quartz lithic assemblages, which archaeologists argue show structural stasis over time. The remaining variability is explained with a 'distance to source' model in which near-coastal sites tend to show a lack of quartz conservation while interior sites show quartz recycling. Under this model, technological strategies traditionally associated with raw material conservation (e.g., bipolar reduction) should not occur at near-coastal sites. We test the 'distance to source' model by reexamining a quartz lithic assemblage from Eagle's Nest-Long Island's richest Holocene coastal hunter-gatherer site. We find conclusive evidence for bipolar reduction in the site's "block/shatter" materials. Toolmakers used bipolar reduction to conserve raw material. Toolmakers also used anvils and bipolar reduction to open quartz cobbles, to stabilize freehand cores, to efficiently access cutting edges, and possibly to create crushed coarse quartz temper for pottery production. Our results point to previously unrecognized aspects of behavioral variability in the Eagle's Nest lithic assemblage and to possible revision of the 'distance to source' model. Similar variability may be present at other North American sites with quartz "block/shatter" material.